Educating for Moderation: Internalization of Islamic Values in Shaping Religious Tolerance in Vocational High Schools - Dudung Suryana; Fuad Hilmi (STAI Hubbulwathan Duri, 2023)
Research on the internalization of Islamic values in fostering religious moderation against a background of anxiety in the next generation of the nation who is starting to lose Islam as the Indonesian nation due to the invasion of foreign cultures. Vocational high school is a very important level of education in instilling Islam in students. The aim of the research is to foster religious moderation through the internalization of Islamic values. This research uses a descriptive qualitative method. The research subjects were selected by purposive sampling: school principals, teachers and students. Data collection techniques include observation, interviews, and documentation. The research subjects were the head, teachers, and students. Data analysis techniques used data collection, reduction, display, and verification. This research shows that the internalization of Islamic values can create religious moderation. This is evidenced by data verification with a data assessment rubric, that the results of observations, interviews, and documentation show that fostering religious moderation is through the internalization of Islamic values.